2014
DOI: 10.1128/jvi.01068-14
|View full text |Cite
|
Sign up to set email alerts
|

Activation of A 1 -Adenosine Receptors Promotes Leukocyte Recruitment to the Lung and Attenuates Acute Lung Injury in Mice Infected with Influenza A/WSN/33 (H1N1) Virus

Abstract: We have shown that bronchoalveolar epithelial A 1 -adenosine receptors (A 1 -AdoR) are activated in influenza A virus-infected mice. Alveolar macrophages and neutrophils also express A 1 -AdoRs, and we hypothesized that activation of A 1 -AdoRs on these cells will promote macrophage and neutrophil chemotaxis and activation and thereby play a role in the pathogenesis of influenza virus-induced acute lung injury. Wild-type (WT) C57BL/6 mice, congenic A 1 -AdoR knockout (A 1 -KO) mice, and mice that had undergone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 85 publications
4
53
1
Order By: Relevance
“…While not included in this list, induction of acute lung injury using influenza virus instillation also has been well established T. Xu et al 2006;Traylor, Aeffner, and Davis 2013;Zhang et al 2012;Aeffner, Woods, and Davis 2014;Dai et al 2014). These models may be used in tandem.…”
Section: Principal Features Used To Define Ards In Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…While not included in this list, induction of acute lung injury using influenza virus instillation also has been well established T. Xu et al 2006;Traylor, Aeffner, and Davis 2013;Zhang et al 2012;Aeffner, Woods, and Davis 2014;Dai et al 2014). These models may be used in tandem.…”
Section: Principal Features Used To Define Ards In Animal Modelsmentioning
confidence: 99%
“…Later, the remaining cells or a portion of them can be processed as cytospin preparations (by centrifugation at 1,000 rpm for 5 min on a Cytospin™ 4 unit; Thermo Fisher Scientific, Waltham, MA) and dyed with Wright-Giemsa stain or a similar method. Differential cell counts typically are performed at 10 (ocular) Â 100 (objective) magnification via oil-immersion microscopy by counting a minimum of 200 cells (optimal: 300 or more cells; Naito et al 2013;McGarry, Protherone, and Lee 2009;Aeffner, Woods, and Davis 2014).…”
Section: Main Feature: Measurements Of the Inflammatory Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Matsumoto et al revealed the presence of abundant vascular stem cells with a characteristic expression of CD34+ in the injured ACL tissues, which displayed higher expansion and multiple lineage differentiation potential than CD34-cells [39]. In a further study, ACL-derived CD34+ cells were injected into nude mice articular cavities after ACL reconstruction, where more fibrocartilage cells, as well as enhanced angiogenesis and osteogenesis, were suggested in a CD34+ sorted group [38]. Additionally, CD34+ cells were previously isolated from peripheral blood or bone marrow and recognised as a rich population of haematopoietic/endothelial progenitor cells, which have been already used in clinical settings for the repair of various damaged tissues [40].…”
Section: Cell-based Therapymentioning
confidence: 99%
“…ACL-derived CD34+ cells have been shown to enhance tendon-bone healing in ACL reconstruction animal models, mostly by enhancing angiogenesis and osteogenesis [37,38]. Matsumoto et al revealed the presence of abundant vascular stem cells with a characteristic expression of CD34+ in the injured ACL tissues, which displayed higher expansion and multiple lineage differentiation potential than CD34-cells [39].…”
Section: Cell-based Therapymentioning
confidence: 99%